Achieving customers' repurchase intention through stimuli and site attachment. Issue 3 (2nd July 2020) - Prodanova, Jana; San-Martín, Sonia; Jiménez, Nadia
ABSTRACT: Despite its widespread use as a purchase channel, the Internet still provokes consumer concerns when it comes to the acquisition of high-involvement services, such as travel. This study, therefore, explores customers' intentions to repeat their online travel purchases, depending on the level of attachment they develop with a website, as is driven by high- and low-task relevant website characteristics. With an innovative, electronic Stimulus–Organism–Response model that introduces a new site attachment variable, this study reveals that, among experienced online travel purchasers, service quality, security and privacy issues, and entertainment all function as stimuli to incite affective, cognitive, and social activity and thereby enhance site attachment. This site attachment, in turn, evokes beneficial customers' responses, in the form of increased intentions to purchase travel services online again. With this distinctive approach to observing customers' reactions to and interaction with websites, this study establishes several strategic implications that can help companies enhance their service features and provision, as well as ensure lasting relationships with their customers.